Expression of human telomerase reverse transcriptase (hTERT) in endometrium during menstrual cycle - Wlaźlak, Edyta; Bitner, Adam; Surkont, Grzegorz; Juszczyszyn-Różycka, Nina; Stetkiewicz, Tomasz; Hendzel, Katarzyna; Kobos, Józef; Suzin, Jacek (Menopause Review/Przegląd Menopauzalny, 2007)
Telomerase is a protein polymerase which has the ability to elongate telomers. There is a common opinion that it plays a crucial role in holding proliferative activity of cells. Aim of the study: The aim of the study was to evaluate telomerase expression in women’s endometrium in proliferative and secretory phase. Material and methods: Telomerase expression was evaluated using monoclonal antibodies against protein subunit of human telomerase (hTERT). In a given range we counted cell index (percentage of cells showing telomerase activity out of all cells). Results: We found significant telomerase expression in every examined tissue. The level of telomerase expression in proliferative endometrium was statistically significantly higher than in the secretory phase. Conclusions: In endometrium of menstruated women there was found high telomerase expression, whose value depended on the phase of the cycle. In the proliferative phase expression was statistically higher than in the secretory phase.